Overtime Assignment and Job Satisfaction in Noise-Safe Job Rotation Scheduling - Rerkjirattikal, Pavinee; Olapiriyakul, Sun (Integrated Uncertainty in Knowledge Modelling and Decision Making, 2019)
Under a harsh industrial environment, workforce safety, and satisfaction are key characteristics of a successful manufacturing operation. This paper proposes a job rotation approach that schedules workers based on NIOSH’s noise-exposure criteria and worker satisfaction related to overtime assignments. Multi-period noise-safe job rotation models are developed to determine optimal job rotation schedules for a heterogeneous workforce with different skill levels and preferences for preferred overtime periods. Demand requirements and the effect of job rotation on process continuity are considered. A numerical example is used to validate the usefulness and effectiveness of the proposed models. The scheduling models are solved under two main objectives: minimizing the total labor cost and maximizing the minimum level of worker satisfaction. Then, a multi-objective optimization technique is applied to find the most suitable compromise solution between the two objectives. The ability of the proposed models to promote worker-satisfaction equality is discussed.